Our colonial year - Harness, Cheryl (Simon & Schuster Books for Young Readers, 2005)
In Colonial America there were no big grocery stores. No microwaves to serve up dinner piping hot. And no dishwashers for cleaning up. So what chores did colonial children do? From quilting bees and maple sugaring in winter, to tilling the earth in spring, to harvesting an autumn feast, storyteller and historian Cheryl Harness tells a month-by-month story of a brand-new nation and the children in every city and farm whose hard work built America. Readers of all ages will delight in this vibrant folk art chronicle of one indelible nation way back when.